Studi Analisis Preferensi Strategi Coping dalam Pemeliharaan Kesehatan Mental Siswa SMA - Hartanto, Dody; Fauziah, Mufied; Kusumaningtyas, Dian Artha; Nugraha, Ariadi; Syifa, Alya Azkia (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to (1) identify and categorize coping strategies used by high school students and (2) analyze the patterns of preference and effectiveness of these strategies based on students' perceptions. This research employs a qualitative approach with an exploratory design. The participants consisted of 647 high school students aged 15–18 years, selected using random sampling from Yogyakarta and Pontianak. The data collection utilized open-ended questionnaires exploring coping strategies for maintaining mental health. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. A hybrid coding system (deductive-inductive) was applied, with credibility ensured through methodological triangulation, member checks, and systematic audit trails. Results revealed that the majority of students preferred positive coping strategies, with refreshing and social support as dominant choices. However, a significant proportion of negative coping strategies was identified, highlighting the need for further guidance. Additionally, the low percentage of professional help-seeking (5.1%) suggests potential barriers in accessing or recognizing mental health services. These findings provide valuable insights for developing targeted intervention programs to support adolescent mental health.